Características pedológicas y utilización de algunos suelos halomórficos de los Bajos Submeridionales, Argentina - Morrás, H.J.M.; Perman, S. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
A sequence of fond soil profiles from the Bajos Submeridionales, Argentina, permitted to distinguish different degrees of pedologic evolution and salinity in relation to the topographic situation of each profile. The analytical data allow us to classify the profiles situated in the “transitional zone” as alkali soils and those situated in the “low zone" as saline-alkali soils The agricultural capability of these soils is discussed on the basis of results obtained diving the study.